2017
DOI: 10.1097/yic.0000000000000145
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vilazodone on sexual functioning in healthy adults

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Table 2 indicates presumed mechanism of interference with sexual response with different classes of antidepressants as well as approximate risk of medication-associated dysfunction. 7283…”
Section: Antidepressant Induced Sexual Dysfunctionmentioning
confidence: 99%
“…Table 2 indicates presumed mechanism of interference with sexual response with different classes of antidepressants as well as approximate risk of medication-associated dysfunction. 7283…”
Section: Antidepressant Induced Sexual Dysfunctionmentioning
confidence: 99%
“…Strikingly, the effect of gender was not investigated in relation to functional MRI (fMRI) measures in any trial. Further, two trials found no differences between men and women, but noted that the sample sizes were not large enough to conclude absence of gender differences in the observed effects (Clayton et al, 2017; Riedel et al, 2005). Thus, several effects of SSRI differed for the sexes but only five trials adjusted the statistical models for gender (Besnier et al, 2010; Knorr, Koefoed, Soendergaard, et al, 2016; J.…”
Section: Resultsmentioning
confidence: 93%
“…The newly retrieved trials and the trials from a previously published systematic review from our group in 2009 (Knorr & Kessing, 2010) resulted in a total of 51 trials (Abler, Grön, Hartmann, Metzger, & Walter, 2012; Abler et al, 2011; Allen, Lader, & Curran, 1988; Almeida et al, 2010; A. N. Simmons, Arce, Lovero, Stein, & Paulus, 2009; Arce, Simmons, Lovero, Stein, & Paulus, 2008; Besnier et al, 2010; Bilderbeck et al, 2014; Briscoe, Ertl, Tate, Dawling, & Davis, 2008; Browning et al, 2011; Bui et al, 2013; Carpenter et al, 2011; Chial et al, 2003; Clayton et al, 2017; Di Simplicio, Doallo, et al, 2014; Di Simplicio, Norbury, & Harmer, 2012; Di Simplicio, Norbury, Reinecke, & Harmer, 2014; Drueke et al, 2009, 2010; Fairweather, Pozzo, Kerr, Lafferty, & Hindmarch, 1997; Fisher et al, 2015; Gerdelat-Mas et al, 2005; Graf, Abler, Hartmann, Metzger, & Walter, 2013; Graf, Metzger, Walter, & Abler, 2016; Grillon, Chavis, Covington, & Pine, 2009; Haahr et al, 2014; Haastrup, Knorr, Erikstrup, Kessing, & Ullum, 2012; Harmer, Mackay, Reid, Cowen, & Goodwin, 2006; Harmer et al, 2004; Hergovich et al, 2000; Hinkelmann et al, 2010; J. G. Simmons & Allen, 2011; J.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 49 Weight gain in the long-term MDD study was small (mean increase +1.7 kg), 49 in contrast to mean weight gains seen in long-term studies of other SSRI drugs (up to ~10 kg). 50 Additionally, vilazodone had no significant placebo-subtracted effect on sexual functioning in patients with MDD 51 or in healthy adult volunteers, 52 which is an important factor to consider when treating patients with sexual dysfunction associated with antidepressant treatment or with depressive disorder itself.…”
Section: Introductionmentioning
confidence: 99%